Comparative study of different ways of treatment on genital wart - Isolan, Tomaz B. (2004)
Introduction: actualy, the Human Papilomavirus (HPV) genital infection is the most prevalent STD in diferents groups and in the great part ofHealth Public Units..Usually is STD that can associate with others genital infecction. Objective:to observate the associate occurence with Siphilis.Methods:a hundred pacients with genital wart were studied in a duble blind, comparative study with randomly select study. The diagnose was madewith clinical examination, hystopatologic and in some of them with HPV 6, 11, 16, 18 DNA molecular hibridization. The pacients were divided infour groups : Group A (25 pacients) were treated with cauterization of the lesion . Group B (25 pacients) were treated with 20.000.000 UI of interfer-on alfa-2B that were applicated in abdominal subcutaneous skin, using 2.500.000 UI in every other day (8 application in the total). Group C (25pacientes ) that A+B were used. Group D (25 pacients) using placebo.. It was considered cure criteriun the pacients that apresented no suspect lesionsafter genital exam in a period of 6 months after the treatment. Blood for siphilis sorology was colected before begining the treatment. Only pacienteswith external lesions participated of the study.. Results: the cure tax of the groups were : Group A - 56%, Group B – 48%, Group C – 76% andGroup D – 4%. The Siphilis sororeativity was 4%. Seventy – two men and twenty – eight women were attended. Conclusion: basing in this nunberswas possible to conclude that treating patients with genital wart is a dificult task in the most cases. In our results, the best tax of cure occurred when itwas associeted in cutting, base cauterization and sistemic administration of interferon alfa-2B.